Authentication of student's assignments - Mateljan, Vladimir (Array, 2009)
The paper proposes a method for determining the originality of student’ s assignments. The method uses a hash algorithm to compare file contents of all students, calculating and showing their similarity. The method is applicable to text files only, and shows the best results when analysing code written in any programming language.